Revisiting Translation of Local Culture: The Case of Madura - Masduki, Masduki; Syifauddin, Moh (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
Cultural translation is a complex process that involves transferring messages between two linguistic codes while considering the sociocultural contexts of both the source and target languages. It requires a holistic approach to navigate various challenges and ensure meaning equivalence. One key perspective in translation studies is the examination of translation through the lens of specific cultural concepts. This study explores the dynamic relationship between translators, the translation of culturally specific expressions, and the quality of the translated work. Understanding cultural nuances is essential, as language is deeply intertwined with the values, traditions, and worldviews of a community. Translators must not only have linguistic proficiency but also possess cultural awareness to convey meaning accurately. Inadequate cultural adaptation may lead to misinterpretation, loss of meaning, or even offense in the target language. Thus, cultural translation requires strategies that balance fidelity to the source text with the naturalness and clarity needed for target readers.This article presents findings from research analyzing the translation of Madurese cultural expressions into English. The study examines distinctive cultural expressions found in Madura, the strategies translators employ to convey these expressions, and the impact of these strategies on message transfer and translation quality. The research draws data from translators working in local government, private sectors, and educational institutions, as well as from official and unofficial documents containing Madurese cultural expressions. Data collection methods include document analysis, questionnaires, and in-depth interviews, analyzed using an interactive model.